2009
DOI: 10.1098/rsbl.2009.0342
|View full text |Cite
|
Sign up to set email alerts
|

How universal are human mate choices? Size does not matter when Hadza foragers are choosing a mate

Abstract: It has been argued that size matters on the human mate market: both stated preferences and mate choices have been found to be non-random with respect to height and weight. But how universal are these patterns? Most of the literature on human mating patterns is based on post-industrial societies. Much less is known about mating behaviour in more traditional societies. Here we investigate mate choice by analysing whether there is any evidence for non-random mating with respect to size and strength in a forager c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 16 publications
3
75
1
Order By: Relevance
“…We did observe that preferred height differences were associated with (perceived) actual partner height differences in both men and women, suggesting that those who preferred a larger SDS also were in a relationship with a relatively large SDS. Interestingly, in a previous study conducted in the Hadza, Sear and Marlowe (2009) reported no evidence of a male-taller norm in this tribe, but they have been collecting their data since 1995, so there might have been some cultural changes with this regard during the last 20 years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We did observe that preferred height differences were associated with (perceived) actual partner height differences in both men and women, suggesting that those who preferred a larger SDS also were in a relationship with a relatively large SDS. Interestingly, in a previous study conducted in the Hadza, Sear and Marlowe (2009) reported no evidence of a male-taller norm in this tribe, but they have been collecting their data since 1995, so there might have been some cultural changes with this regard during the last 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…They number approximately 1,000-1,500 individuals and live in mobile camps, each comprising 30 people on average. This society has been extensively described in the literature (see Marlowe, 2010;Sear and Marlowe, 2009;Butovskaya, 2013). Women typically marry between 17 and 18 years of age, and men marry around the age of 20.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations